Esterházy János felvidéki magyar politikus munkássága, elítélése és a szovjetunióbeli gulágon eltöltött évei - Janek István („RIK-U” Kiadó, 2017)
Esterházy János gróf 1901. március 14-én született Nyitraújlakon, régi történelmi családban, a galántai Esterházyak cseszneki ágához tartozott. Dédapja báró Jeszenák János nyitrai kormánybiztos volt, aki részt vett az 1848-as magyar szabadságharcban, és akit 1849-ben a császáriak kivégeztek. Apja, Esterházy János korán meghalt, édesanyja Tarnowska Erzsébet lengyel grófnő volt, aki özvegyként két testvérével együtt nevelte Esterházyt. A család mintegy 5000 holdnyi földterületet tudhatott magáénak, amelynek egy része Magyarországon, de a nagyobbik része Csehszlovákiában volt. 1919-ben a csehszlovák földreform következtében birtokaik egy része elveszett. A fiatal Esterházy Budapesten járt gimnáziumba és ott kereskedelmi akadémiát végzett, ezután a saját birtokán gazdálkodott Nyitraújlakon. 1924-ben feleségül vette Serényi Lívia grófnőt, akitől két gyermeke született, János és Alice.

Abstract. The purpose of this study is the introduction of the mediation of János Esterházy in the bilateral relations of Slovakia and Hungary mentioning only a few examples due to limitations in length. In the second part of the study, the activity of Esterházy in the Jewish question is discussed; the reasons behind his voting against the Jewish law. János Esterházy considered it his main goal to forge the Hungarian minority in Slovakia together, and he imagined the life of the community in the form of a great family. The person of Esterházy is interpreted in different ways in the Slovak and Hungarian history writing. As president of the Hungarian Party he regularly visited Hungarian towns and villages and he endeavoured to remedy the grievances of the local people. He also played a key role in the development of bilateral connections and diplomatic negotiations in 1939-1944. Hungarian and Slovak politicians asked for his opinion in every important case, and he also mediated between the two countries. He maintained good connections with the highest Hungarian and Slovakian circles, and he regularly met with foreign diplomats accredited to Bratislava. He would travel to Budapest where he spoke up not only for the Hungarian minority in Slovakia but also for the Slovakian minority in Hungary. Esterházy’s policy was determined by his Christian Catholic faith, his minority consciousness and social sensitivity. These three elements formed the fundaments of his Christian social conception. His Christianity meant charity, social responsibility and the protection of the weak and the persecuted. In order to understand his personality, it must be emphasised that he had solid moral principles. In the third part of the study, is about Esterházy’s life from 1945 to 1957. Also in this part treats with his life in Gulág and his legal proceeding in Sovietunion and Czechoslovakia.
Activity, conviction and years on the soviet gulag of János Esterházy, the hungarian politician of upper hungary
https://kmf.uz.ua/hu/kiadvanyaink/hadifogsag-malenkij-robot-gulag-karpat-medencei-magyarok-es-nemetek-elhurcolasa-szovjetunio-hadifogolyes-kenyszermunkataboraiba-1944-1953/
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00004138
Keywords: Esterházy János; zsidótörvény; gulág